Altered sleep architecture in diabetes and prediabetes: findings from the Baependi Heart Study - Chen, Daniel M; Taporoski, Tâmara P; Alexandria, Shaina J; Aaby, David A; Beijamini, Felipe; Krieger, Jose E; von Schantz, Malcolm; Pereira, Alexandre; Knutson, Kristen L (medRxiv : the preprint server for health sciences, 2023)
People with diabetes are more likely to have obstructive sleep apnea, but there are few studies examining sleep architecture in people with diabetes, especially in the absence of moderate-severe sleep apnea. Therefore, we compared sleep architecture among people with diabetes, prediabetes or neither condition, whilst excluding people with moderate-severe sleep apnea. This sample is from the Baependi Heart Study, a prospective, family-based cohort of adults in Brazil. 1,074 participants underwent at-home polysomnography (PSG). Diabetes was defined as 1) FBG>125 OR 2) HbA1c>6.4 OR 3) taking diabetic medication, and prediabetes was defined as 1) [(5.7≤HbA1c≤6.4) OR (100≤FBG≤125)] AND 2) not taking diabetic medication. We excluded participants that had an apnea-hypopnea index (AHI)>30 from these analyses to reduce confounding due to severe sleep apnea. We compared sleep stages among the 3 groups. Compared to those without diabetes, we found shorter REM duration for participants with diabetes (-6.7min, 95%CI -13.2, -0.1) or prediabetes (-5.9min, 95%CI -10.5, -1.3), even after adjusting for age, gender, BMI, and AHI. Diabetes was also associated with lower total sleep time (-13.7min, 95%CI -26.8, -0.6), longer slow-wave sleep (N3) duration (+7.6min, 95%CI 0.6, 14.6) and higher N3 percentage (+2.4%, 95%CI 0.6, 4.2), compared to those without diabetes. People with diabetes and prediabetes had less REM sleep after taking into account potential confounders, including AHI. People with diabetes also had more N3 sleep. These results suggest that diabetes is associated with different sleep architecture, even in the absence of moderate-severe sleep apnea.